Generalized Centroid of Hyperrings - Yazarli Hasret; Davvaz Bijan; Yilmaz Damla (Discussiones Mathematicae - General Algebra and Applications, 2022)
In this paper, the notion of generalized centroid is applied to hyperrings. We show that the generalized centroid C of a semiprime hyperring R is a regular hyperring. Also, we show that if C is a hyperfield, then R is a prime hyperring.